Tree Planting To Encourage Ecotourism Concept on Penyengat Island - Ranti Utami; Djoko Suhardjanto; Wahyu Widarjo; Marhalinda Marhalinda; Budi Alamsyah Siregar; Mohd Koharuddin; Mohamed Ayyub Hassan (International Journal of Community Engagement and Development, 2023)
Penyengat Island is an island that has historical and religious tourism destinations. Penyengat Island is an island surrounded by sea and has quite a large population. Ecotourism is part of tourist attractions that utilize the potential of local natural resources, and are developed with environmentally friendly innovation and technology. This activity aims to provide benefits that can be felt directly and indirectly. The stages carried out in tree planting activities consist of socializing the need for a greening movement, preparing tree planting locations and carrying out mangrove seedling planting activities. With tree planting activities, many benefits can be obtained, such as a greener environment, keeping the air clean, protecting the coast from erosion and strong wave attacks, helping to reduce the risk of flooding in coastal areas and planting mangrove trees can prevent abrasion.